Discontinuous dynamic equations on time scales - dos Santos, Iguer Luis Domini [UNESP] (Springer Nature, 2015)
We introduce and prove the existence of Hermes, Filippov, and Krasovskii generalized solutions to discontinuous dynamic equations on time scales. We also consider comparisons between the Carathéodory, Euler, Filippov, Hermes, and Krasovskii generalized solutions to discontinuous dynamic equations on time scales.
Keywords: Dynamic equations; Generalized solutions; Initial value problems; Time scales